Linkage analysis of peripheral neurofibromatosis to DNA markers on chromosome 8. Issue 9 (September 1987) - Diehl, S R; Boehnke, M; Collins, F S; Erickson, R P; Karolyi, I J; Ploughman, L M; Pericak-Vance, M A; Aylsworth, A S; Roses, A D
Abstract : Linkage relationships of the gene for peripheral neurofibromatosis (NF) were assessed in a large American Caucasian pedigree using two DNA markers located on chromosome 8. Linkage to the thyroglobulin locus, located at 8q24, was excluded (lod less than or equal to -2.0) to 21 cM. Data obtained for the tissue plasminogen activator locus, located at 8p12, excluded linkage to 4 cM. These results exclude between 20 to 30% of chromosome 8 as a possible map location for the NF gene in this family. Comparison of the two DNA markers excluded their linkage to 0.5 cM.